2021
DOI: 10.5588/ijtld.21.0278
|View full text |Cite
|
Sign up to set email alerts
|

The burden and determinants of post-TB lung disease

Abstract: BACKGROUND: Post-TB lung disease (PTLD) is an important but under-recognised chronic respiratory disease in high TB burden settings such as Tanzania.METHODS: This was a cross-sectional survey of adults within 2 years of completion of TB treatment in Kilimanjaro, Tanzania. Data were collected using questionnaires (symptoms and exposures), spirometry and chest radiographs to assess outcome measures, which were correlated with daily life exposures, including environment and diet.RESULTS: Of the 219 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
0
21
0
3
Order By: Relevance
“…Up to half of TB survivors have some form of chronic pulmonary dysfunction despite microbiologic cure, impairing their quality of life. 5 11 These post-TB consequences are likely to impose a continued financial burden on TB survivors, their families, their communities and the health system. 5 The WHO defines health as a state of ‘complete physical, mental and social well-being’.…”
Section: Post-tb Economic Social and Psychological Wellbeingmentioning
confidence: 99%
“…Up to half of TB survivors have some form of chronic pulmonary dysfunction despite microbiologic cure, impairing their quality of life. 5 11 These post-TB consequences are likely to impose a continued financial burden on TB survivors, their families, their communities and the health system. 5 The WHO defines health as a state of ‘complete physical, mental and social well-being’.…”
Section: Post-tb Economic Social and Psychological Wellbeingmentioning
confidence: 99%
“…We examined data from the subset of six studies that enrolled some patients who had received retreatment for TB along with first time TB patients, and found that retreatment patients comprised a minority of the study population in five of the six studies [25,28,36,41,44,50]. However, one study [41] exclusively enrolled retreatment TB patients.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…(3) A tuberculose afeta predominantemente os pulmões, e muitos pacientes, não obstante a cura confirmada bacteriologicamente, terão sequelas da tuberculose, com perda da função pulmonar e sintomas respiratórios crônicos, além de diminuição da capacidade de exercício e da qualidade de vida. (4)(5)(6)(7)(8)(9)(10) A prevalência de sequelas pulmonares da tuberculose (SPTB) varia muito, de 18% a 87%, (11) dependendo da população estudada e dos testes de função pulmonar realizados.…”
Section: Introductionunclassified